KONFLIK PERDAGANGAN INDONESIA –CHINA - Ferry Samuel Jacob (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2007)
Trade relation between Indonesia and china has faced a certainty constraint. It emeged when the government of Indonesia and China at almost the same time released a public warning and import restriction from each country, there is a worry it would become the central issue of the happening of broader tradeconflic t. A problem actually , was not an action of reciprocating of government of Indonesia and China. It would rather show the problem of product standardization especially concerned health standard .Each country claims the hazardous substances contained in a certainty product which could bring one of the worst diseases for humam health. Moreover, the standard which claimed by both countries based on the product standard applying in each country and has been confessed internationally. Both Indonesia and China was going to solve the problem bilaterally (G to G). Therefore , the conflict will increase the cost of opportunity higher than the benefit for Indonesia and China.